PENGOLAHAN DATA AKUNTANSI MENGGUNAKAN MYOB V16 PADA CV. OPTIK BONIE JAKARTA BARAT. - Mujiaty, Yulia; Vidada, Irwin Ananta; Saridawati, Saridawati; Novayanti, Deasy; Irwandy, Ade (Aksara Public, 2019)
In the current era of globalization, technology is growing rapidly and is a demand for companies requiring accounting systems that can produce financial statement information. CV. Optik Bonie is a company engaged in trading and still uses the system manually in the process of making financial reports starting from recording cash receipts, cash disbursements, sales, purchases and receipt of repayment of accounts receivable to financial statements making. This makes it possible at the time of the process to occur an error in recording, inaccurate reports made and delays in searching for the required data. The application of accounting applications using Myob Premier V.16 is a solution to solve problems that exist in the company and with a computerized system that can make activities effective and efficient compared to manual methods.